Decorative pictures and emotional design in multimedia learning. (August 2016) - Schneider, Sascha; Nebel, Steve; Rey, Günter Daniel
Abstract: Recent studies have shown that the positive emotional design of learning environments might foster learning performance. In contrast, the seductive detail effect postulates that additional, learning irrelevant details inhibit learning. This research focusses on the implementation of decorative pictures as a prime for emotions and context-relatedness. This study examines four groups of decorative pictures which might be conducive for learning. Eighty-two students were randomly assigned to one cell of a 2 (emotionally positive vs. emotionally negative pictures) × 2 (school context vs. leisure context pictures) between-subjects, factorial design. The dimensions of pleasure, arousal, and dominance are examined as possible mediators. Results show that either positively valenced pictures or learning pictures foster retention and transfer performance. Pleasure is identified as mediator of the effect between valence of pictures and learning performance. A further analysis shows differences for arousal and dominance for both factors. These results are interpreted with concepts like motivated attention and other arousal theories. Highlights: Decorative pictures serve different functions in multimedia learning. Learning context foster learning in contrast to leisure context pictures. Positively valenced pictures enhance learning more than negative pictures. Pleasure functions as a mediator between valence and learning performances. Learning context and valence influence arousal and dominance perceptions.